Novel Indigenous Probiotic Lactobacillus reuteri Strain Produces Anti-biofilm Reuterin against Pathogenic Periodontal Bacteria - Widyarman, Armelia Sari; Theodorea, Citra Fragrantia (European Journal of Dentistry, 2021)
Objective The aim of this study was to evaluate the effect of reuterin produced by a novel probiotic strain of Lactobacillus reuteri against periodontal biofilms.Materials and Methods L. reuteri LC382415 (an indigenous Indonesian strain) was cultured in Man, Rogosa, and Sharpe (MRS) agar in anaerobic conditions for 24 hours. To isolate reuterin, L. reuteri was suspended in 300-mM glycerol in MRS broth and incubated under anaerobic conditions for 3 hours, and the supernatant fraction was filtered. The presence of reuterin was confirmed by sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE), and its concentration was determined. The effect of reuterin on Porphyromonas gingivalis ATCC 33277 and T. denticola ATCC 35405 biofilms was evaluated using biofilm assays. Biofilms were formed by incubating bacteria in 96-well microplates for 48 hours. A dose-dependent experiment was performed with reuterin concentrations of 12.5, 25, 50, and 100 μg/mL on biofilms. The inhibitory effect was measured at 1, 3, 6, and 24 hours. The biofilm masses were measured at 490 nm. Statistical analysis was using one-way ANOVA.Results The SDS-PAGE assay confirmed the presence of reuterin (52 kDa) in the culture supernatant of the L. reuteri strain. Reuterin in a concentration as low as 12.5 μg/mL significantly inhibited single- and mixed-species biofilms (p < 0.05).Conclusions This is the first study to demonstrate the promising effect of reuterin isolated from L. reuteri LC382415 against periodontal bacteria. Further studies are warranted to explore the mechanism of this active component.
Keywords: biofilm; Lactobacillus reuteri; Porphyromonas gingivalis; reuterin; Treponema denticola